Spirituality and nursing: a reductionist approach - Paley, John (Nursing philosophy, 2008)
The vast majority of contributions to the literature on spirituality in nursing make extravagant claims about transcendence, eternity, the numinous, higher powers, higher levels of existence, invisible forces, cosmic unity, the essence of humanity, or other supernatural concepts. Typically, these assertions are made without the support of argument or evidence; and, as a consequence, alternative ways of theorizing ‘spirituality’ have been closed off, while the lack of consistent scholarship has turned the topic into a metaphysical backwater. In this paper, I adopt a different premise, rejecting unsupported claims, and surveying the ‘spirituality’ terrain from a naturalistic and reductionist perspective. I argue that, if we rid ourselves of non-naturalistic assumptions, we will discover theoretical and clinical resources in health psychology, social psychology, neuropsychology, and pharmacopsychology - resources which confirm that it is possible to conceptualize the study of existential concerns, and how health professionals might respond to them, in a properly scientific manner. In order to illustrate the potential usefulness of these resources, I will take palliative care as an example.